2018
DOI: 10.1155/2018/4769596
|View full text |Cite|
|
Sign up to set email alerts
|

SIRT7 Regulates the Vascular Smooth Muscle Cells Proliferation and Migration via Wnt/β-Catenin Signaling Pathway

Abstract: A huge amount of evidence indicates that sirtuin 7 (SIRT7), a key mediator of many cellular activities, plays a crucial role in the pathogenesis of various diseases. However, little is known about the role of SIRT7 in atherosclerosis. This study investigated the potential role of SIRT7 in regulating the proliferation and migration of human vascular smooth muscle cells (HAVSMCs) and its possible molecular mechanism. In this study, human vascular smooth muscle cells (HAVSMCs) were induced by oxidized low-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 36 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…It is well known that aberrant proliferation and migration of VSMCs play an important role in the pathogenesis of AS [5]. Evidence indicates that miR-183-5p has a regulatory effect on cellular behaviors, and further participates in the pathogenesis of human diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that aberrant proliferation and migration of VSMCs play an important role in the pathogenesis of AS [5]. Evidence indicates that miR-183-5p has a regulatory effect on cellular behaviors, and further participates in the pathogenesis of human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that vascular smooth muscle cells (VSMCs) play an important role in the pathological progress of AS [4]. The aberrant behaviors of VSMCs participate in the pathobiology of AS, and are related to other cellular processes such as inflammation, apoptosis and matrix alterations [5].…”
Section: Introductionmentioning
confidence: 99%
“…During the past few decades, they mainly focused on developing algorithms such as level set, watershed, statistical shape model, region growing, active contour model, threshold processing, graph cuts and traditional machine learning methods that require manually extract tumor features. For example, Zhou et al [1] proposed a unified level set method (LSM) for liver tumor segmentation. They used local pixel intensity clustering combined with hidden Markov random field to construct a unified LSM.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, abnormal activation or inhibition of the Wnt/β-catenin pathway has been associated with the occurrence of various diseases, including cancers and Parkinson’s disease [11]. In recent years, an increasing number of reports have shown that this pathway is associated with EC dysfunction and AS [13,14]. For example, Wnt-5a protein expression was significantly up-regulated during AS development and was positively correlated with AS severity in animal experiments and human endarterectomy samples [15,16].…”
Section: Introductionmentioning
confidence: 99%